Selecting Evidence-Based Content for Inclusion in Self-Management Apps for Pressure Injuries in Individuals With Spinal Cord Injury: Participatory Design Study - Fiordelli, Maddalena; Zanini, Claudia; Amann, Julia; Scheel-Sailer, Anke; Brach, Mirjam; Stucki, Gerold; Rubinelli, Sara (JMIR Publications, 2020)
BackgroundTechnological solutions, particularly mobile health (mHealth), have been shown to be potentially viable approaches for sustaining individuals' self-management of chronic health conditions. Theory-based interventions are more successful, as evidence-based information is an essential prerequisite for appropriate self-management. However, several reviews have shown that many existing mobile apps fail to be either theoretically grounded or based on evidence. Although some authors have attempted to address these two issues by focusing on the design and development processes of apps, concrete efforts to systematically select evidence-based content are scant. ObjectiveThe objective of this study was to present a procedure for the participatory identification of evidence-based content to ground the development of a self-management app. MethodsTo illustrate the procedure, we focused on the prevention and management of pressure injuries (PIs) in individuals with spinal cord injury (SCI). The procedure involves the following three steps: (1) identification of existing evidence through review and synthesis of existing recommendations on the prevention and self-management of PIs in SCI; (2) a consensus meeting with experts from the field of SCI and individuals with SCI to select the recommendations that are relevant and applicable to community-dwelling individuals in their daily lives; and (3) consolidation of the results of the study. ResultsIn this case study, at the end of the three-step procedure, the content for an mHealth intervention was selected in the form of 98 recommendations. ConclusionsThis study describes a procedure for the participatory identification and selection of disease-specific evidence and professional best practices to inform self-management interventions. This procedure might be especially useful in cases of complex chronic health conditions, as every recommendation in these cases needs to be evaluated and considered in light of all other self-management requirements. Hence, the agreement of experts and affected individuals is essential to ensure the selection of evidence-based content that is considered to be relevant and applicable.